Global Health in the Age of COVID-19: Responsive Health Systems Through a Right to Health Fund - Eric A. Friedman; Lawrence O. Gostin; Allan Maleche; Alessandra Nilo; Fogue Foguito; Umunyana Rugege; Sasha Stevenson; Githinji Gitahi; Ana Lorena Ruano; Michele Barry; Sara Hossain; Franciscka Lucien; et al. (Harvard FXB Center for Health and Human Rights, 2020)
We propose that a Right to Health Capacity Fund (R2HCF) be created as a central institution of a reimagined global health architecture developed in the aftermath of the COVID-19 pandemic. Such a fund would help ensure the strong health systems required to prevent disease outbreaks from becoming devastating global pandemics, while ensuring genuinely universal health coverage that would encompass even the most marginalized populations. The R2HCF's mission would be to promote inclusive participation, equality, and accountability for advancing the right to health. The fund would focus its resources on civil society organizations, supporting their advocacy and strengthening mechanisms for accountability and participation. We propose an initial annual target of US$500 million for the fund, adjusted based on needs assessments. Such a financing level would be both achievable and transformative, given the limited right to health funding presently and the demonstrated potential of right to health initiatives to strengthen health systems and meet the health needs of marginalized populations-and enable these populations to be treated with dignity. We call for a civil society-led multi-stakeholder process to further conceptualize, and then launch, an R2HCF, helping create a world where, whether during a health emergency or in ordinary times, no one is left behind.